American Geographical Society of New York world 1:5,000,000 - American Geographical Society of New York (American Geographical Society of New York, 1964)
Relief shown by gradient tints and spot heights. Depths shown by gradient tints, contours and soundings. Composite series. Sheet numbering 1-15 varies with edition. Special composite sheet of the Arctic Region. Includes index maps and text. Standard map series designation: Series 1106. Color 1:5,000,000